Subregional Differences in Alcohol Modulation of Central Amygdala Neurocircuitry - Melkumyan, Mariam; Silberman, Yuval (Frontiers in Molecular Neuroscience, 2022)
Alcohol use disorder is a highly significant medical condition characterized by an impaired ability to stop or control alcohol use, compulsive alcohol seeking behavior, and withdrawal symptoms in the absence of alcohol. Understanding how alcohol modulates neurocircuitry critical for long term and binge-like alcohol use, such as the central amygdala (CeA), may lead to the development of novel therapeutic strategies to treat alcohol use disorder. In clinical studies, reduction in the volume of the amygdala has been linked with susceptibility to relapse to alcohol use. Preclinical studies have shown the involvement of the CeA in the effects of alcohol use, with lesions of the amygdala showing a reduction in alcohol drinking, and manipulations of cells in the CeA altering alcohol drinking. A great deal of work has shown that acute alcohol, as well as chronic alcohol exposure via intake or dependence models, alters glutamatergic and GABAergic transmission in the CeA. The CeA, however, contains heterogeneous cell populations and distinct subregional differences in neurocircuit architecture which may influence the mechanism by which alcohol modulates CeA function overall. The current review aimed to parse out the differences in alcohol effects on the medial and lateral subregions of the CeA, and what role neuroinflammatory cells and markers, the endocannabinoid system, and the most commonly studied neuropeptides systems play in mediating these effects. A better understanding of alcohol effects on CeA subregional cell type and neurocircuit function may lead to development of more selective pharmacological interventions for alcohol use disorder.